Let the other factor be (x + p)
Then, x2 – 6x – 16 = (x + p)(x + 2)
= x2 + (p + 2)x + 2p
On comparing the coefficients on both sides, we get,
p + 2 = – 6
⇒ p = – 8
∴ The other factor is (x – 8).
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
If one of the facTamilnadu Board Math Term-II